Ru alloying with La or Y for ammonia synthesis via integrated dissociative and associative mechanism with superior operational stability. (28th April 2022) - Zhang, Tianhua; Zhu, Jie; Wang, Junjie; Peng, Xuanbei; Deng, Jinxiu; Wang, Shiyao; Song, Yi; Zhou, Yanliang; Ni, Jun; Wang, Xiuyun; Liang, Shijing; Lin, Xingyi; et al.
Highlights: For the first time, we report the formation of Ru-rare-earth elements (REEs) alloys, which not only maximizes the electronic effect but also endows with a completely new type of active sites. The developed RuLa/HZ catalyst exhibits a NH3 synthesis rate 43.3-fold that of Ru/HZ. We report here for the first time the co-operation of dissociative and associative routes over RuLa/HZ catalyst to achieve unprecedentedly high NH3 synthesis rate. RuLa/HZ exhibits superior operational stability without obvious deactivation in a run of 1756 h (ca.73 days) at 400 °C and 1 MPa. Abstract: The alloying of Ru with rare-earth elements (REEs) is an effective approach for the modification of the electronic structure of Ru. Here, for the first time, we report the formation of Ru-M (M = La or Y) alloys that are endowed with a completely new type of active sites. Over the Ru-M (M = La or Y) catalysts, N2 activation in ammonia synthesis follows neither the well-known dissociative nor the associative route but rather a co-operation of both, leading to outstanding performance. The developed RuLa/HZ catalyst exhibits a NH3 synthesis rate of 14.73 mmol gcat −1 h −1 at 400 °C and 1 MPa without obvious deactivation in a run of 1756 h (ca.73 days).